1997
DOI: 10.1111/j.1469-7793.1997.145bc.x
|View full text |Cite
|
Sign up to set email alerts
|

Local opioid inhibition and morphine dependence of supraoptic nucleus oxytocin neurones in the rat in vivo

Abstract: Single neurones of the rat supraoptic nucleus were recorded during microdialysis of naloxone onto the ventral surface of the nucleus in anaesthetized rats. We used this combination of techniques to test whether the acute or chronic effects of systemically or centrally applied opioids upon oxytocin cell activity were due to actions of the opioids within the nucleus itself. Supraoptic nucleus oxytocin neurones were identified antidromically and by an excitatory response to intravenously injected cholecystokinin.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0
5

Year Published

2003
2003
2017
2017

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 33 publications
1
24
0
5
Order By: Relevance
“…Moreover, we have found that -receptor mRNA is expressed in SON VP neurons and non-VP, presumably oxytocin (OT), neurons. A role for -opioid receptors in OT release has been known for some time, although the specific site, either pre-or postsynaptic, has been difficult to delineate (Falke, 1991;Ludwig et al, 1997). Recently, it has also been demonstrated that VP neurons in the rat SON are directly responsive to -opioid agonist and, therefore, are likely to express -opioid receptors (Soldo and Moises, 1998), in agreement with our current findings in the guinea pig.…”
Section: -Opioid Receptor Mrna In Vp Neuronssupporting
confidence: 89%
See 1 more Smart Citation
“…Moreover, we have found that -receptor mRNA is expressed in SON VP neurons and non-VP, presumably oxytocin (OT), neurons. A role for -opioid receptors in OT release has been known for some time, although the specific site, either pre-or postsynaptic, has been difficult to delineate (Falke, 1991;Ludwig et al, 1997). Recently, it has also been demonstrated that VP neurons in the rat SON are directly responsive to -opioid agonist and, therefore, are likely to express -opioid receptors (Soldo and Moises, 1998), in agreement with our current findings in the guinea pig.…”
Section: -Opioid Receptor Mrna In Vp Neuronssupporting
confidence: 89%
“…Specifically, endogenous opioid peptides, such as met-enkephalin, which can activate -opioid receptors, are known to have powerful inhibitory effects on hypothalamic neurons involved in regulation of LH and prolactin secretion (Leadem and Yagenova, 1987;Kapoor and Willoughby, 1991;Kehoe et al, 1993;Kalra, 1993;Goodman et al, 1995;Walsh and Clarke, 1996;Herbison, 1998). Opioids have also been found to inhibit activity-dependent release of oxytocin and vasopressin from the supraoptic nucleus (SON), which may be at least in part through a -opioid mechanism because the -opioid agonist DAMGO directly attenuates N-and P-type calcium currents in rat SON neurons (Falke, 1991;Ingram et al, 1996;Ludwig et al, 1997;Soldo and Moises, 1998).…”
mentioning
confidence: 98%
“…Our finding provides an underlying cellular mechanism for an inhibitory action of AVP on AVP neurons that would effectively limit the excitation of these neurons (Ludwig and Leng, 1997). …”
Section: Physiological Implicationsmentioning
confidence: 80%
“…Our result supports such a possibility: AVP released within the nucleus would favor an excitation of OXT neurons while causing inhibition of AVP neurons. The activity of AVP neurons is tuned by AVP, so that the neurons would be quieted during high level of activity (Ludwig et al, 1997). In contrast, OXT that may also be released during high activity of the nucleus will further increase the activity of OXT neurons (Yamashita et al, 1987;Moos and Richard, 1989).…”
Section: Avp Differentially Modulates Epscs In Different Populations mentioning
confidence: 99%
“…In virgin rats, µ- and ĸ-agonists reduce the firing rate of oxytocin cells [8]. Naloxone administration into the SON prevents the decrease of firing rate of oxytocin cells occurred with morphine [9]. During spontaneous parturition, fos (protein product of c-fos) is expressed in SON and brainstem neurons [10].…”
Section: Introductionmentioning
confidence: 99%